A framework for making citizen science inclusive with storytelling methods - Veeckman, C.; Claes, S.; Van Audenhove, L.; van der Graaf, S. (Frontiers in Environmental Science, 2023)
Citizen science is challenged by a participation inequality that is not compatible with a democratic approach to science. To include the voices of underrepresented groups, this article presents “STORCIT”, a framework for making citizen science inclusive with storytelling methods. This framework was trialed in the project “Climate Stories” with two small-scale pilot studies in Hasselt and Brussels (Belgium). This project involved around 50 young people with a diverse background, since they are often overlooked as agents of change in the climate debate. During the project, they recorded their experiences related to the changing climate through citizen science and storytelling methods. The STORCIT-framework was designed through five consecutive phases: i) setting the scene, ii) generating knowledge and learning, iii) sharing personal narratives iv) developing stories, and v) exhibiting to the public. The results reflect on the implementation of this approach, together with the experienced challenges, limitations, and gains. Overall, the approach is highly participatory, multi-faceted and supports the democratization of knowledge generation. The gathered knowledge helps participants to reflect on their story, raise their voice and catalyze actions for social change. In the context of citizen science research, practitioners are encouraged to explore and further adapt this framework to other (justice) domains and involve other vulnerable target groups. In particular, it can be deployed by those who aim to include diverse audiences and stimulate inclusive dialogue between science, society and policy with actions for social change.